Opportunity of digital marketing in tourism sphere - Kayumovich, Khurramov Ortikjon; Annamuradovna, Fayzieva Sayyora; Alimovich, Farmanov Erkin; Alisherovna, Djafarova Nigina; Olimovich, Davronov Istamkhuja (International Journal of Psychosocial Rehabilitation, 2020)
This article describes the opportunity of digital marketing in tourism sphere. Since the Internet as a medium of communication is constantly progressing and becoming more complicated, and at the same time, the possibilities of promoting a company in the virtual space are expanding, a need arose for a new direction in the structure of general marketing, which would write the features of achieving the goals of marketing on the Internet.